CIP2A deficiency promotes depression‐like behaviors in mice through inhibition of dendritic arborization. (28th October 2022) - Hu, Wen‐Ting; Liuyang, Zhen‐Yu; Tian, Yuan; Liang, Jia‐Wei; Zhang, Xiao‐Lin; Zhang, Hui‐Liang; Wang, Guan; Huo, Yuda; Shentu, Yang‐Ping; Wang, Jian‐Zhi; Wang, Xiao‐Chuan; Lu, You‐ming; et al.
Abstract: Major depressive disorder (MDD) is a severe mental illness. Decreased brain plasticity and dendritic fields have been consistently found in MDD patients and animal models; however, the underlying molecular mechanisms remain to be clarified. Here, we demonstrate that the deletion of cancerous inhibitor of PP2A (CIP2A), an endogenous inhibitor of protein phosphatase 2A (PP2A), leads to depression‐like behaviors in mice. Hippocampal RNA sequencing analysis of CIP2A knockout mice shows alterations in the PI3K‐AKT pathway and central nervous system development. In primary neurons, CIP2A stimulates AKT activity and promotes dendritic development. Further analysis reveals that the effect of CIP2A in promoting dendritic development is dependent on PP2A‐AKT signaling. In vivo, CIP2A deficiency‐induced depression‐like behaviors and impaired dendritic arborization are rescued by AKT activation. Decreased CIP2A expression and impaired dendrite branching are observed in a mouse model of chronic unpredictable mild stress (CUMS). Indicative of clinical relevance to humans, CIP2A expression is found decreased in transcriptomes from MDD patients. In conclusion, we discover a novel mechanism that CIP2A deficiency promotes depression through the regulation of PP2A‐AKT signaling and dendritic arborization. Synopsis: Mice deficient for the PP2A inhibitor CIP2A show reduced dendritic arborization and develop depression‐like behaviors, which can be rescued by AKT activation. CIP2A deletion induces depression‐like behaviors in mice. CIP2A promotes dendritic arborization and development through activating AKT. PP2A mediates the effects of CIP2A on AKT activation and dendritic development. CIP2A deficiency‐induced depression‐like behaviors and dendrite/spine loss are rescued by AKT activation in mice. CIP2A deficiency and impaired dendritic arborization coexist in brains of rat models of chronic mild stress‐induced depression. Abstract : Mice deficient for the PP2A inhibitor CIP2A show reduced dendritic arborization and develop depression‐like behaviors, which can be rescued by AKT activation.